Determinants of Antenatal Care First Trimester Initiation and their Effects in Place of Delivery in the Builsa South District of the Upper East Region - Boah, M. (University of Ghana, 2016)
The importance of antenatal care and skilled-birth attendant at delivery in the reduction of maternal morbidity and mortality are key components of the safe motherhood initiative. Despite the introduction of strategies to promote early antenatal care attendance and delivery in health facilities by skilled attendants, women in the Builsa South district initiate antenatal care late. The purpose of this study is to explore the determinants of antenatal care first trimester initiation and how they affect the place where the woman delivers. A population based cross sectional study was conducted in June 2016 among four hundred and thirty-one women in childbearing age who delivered in the past six months preceding the survey. Both quantitative and qualitative methods were used in data collection. Four focus discussions were conducted. The study was approved by Ethics Review Committee of the Ghana Health Service. Quantitative data were analyzed using STATA version 13. Pearson Chi- square test was used to identify statistically significant association in a bivariate analysis. A multivariate logistic regression was used to estimate the strength of association between the independent variables and the outcome variables. In the qualitative method, discussions were recorded and transcribed verbatim. Thematic analysis was used for the analysis. The study found 98.8% of the respondents used antenatal care at least once in their recent pregnancy. However, many booked after the first trimester of pregnancy and 68 percent attained four and more visits before delivery. Prevalence of health facility delivery was 62.7 percent. Unaware of delivery onset and no complications with previous delivery were the major causes of home delivery. Maternal age, highest educational attainment, parity, occupation, and having a valid health insurance during pregnancy were significantly associated with the timing of the first antenatal care visit in the bivariate analysis. In the multivariate analysis, level of educational attainment was identified as the determinant of antenatal care initiation which had a statistically significant association (p<0.05) with place of delivery. The frequently mentioned reasons for late booking from the discussions were unplanned pregnancy and waiting to confirm pregnancy status. The findings suggest that there is urgent need to advocate for and invest in the education of the female child since this promotes better maternal health seeking behaviour and can contribute to reducing maternal morbidity and mortality. The qualitative results also suggest that though maternal health services are free for women who deliver in health facilities, there are other hidden costs like the inability to afford Dettol, soap, bleach, and rubber sheets required for delivery which serve as barriers to health facility delivery. Health care providers can identify potential women who will most likely deliver at home using the routinely collected data on the women during antenatal care. Women found to be at risk of home delivery can be supported throughout pregnancy to encourage them to deliver in health facilities with skilled-birth attendants.
Thesis(MPH)-University of Ghana, 2016
Keywords: Antenatal Care First Trimester Initiation; Determinants